2008
DOI: 10.1111/j.1745-4522.2008.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Carotenoid and Flavonoid Components in Brans of Some Thai Black Rice Cultivars Using Supercritical Fluid Extraction and High‐performance Liquid Chromatography‐mass Spectrometry

Abstract: A method employing supercritical fluid extraction (SFE) followed by high‐performance liquid chromatography‐electrospray ionization‐mass spectrometry (LC‐ESI‐MS) was developed and used for quantification of the antioxidants in groups of carotenoids and flavonoids in the bran of four Thai black rice cultivars: Kao Hom Nin BD, Kao Hom Nin BT, Kao Hom Nin BT no. 3 and 1000–11–2–26. Trans‐β‐carotene, quercetin and isorhamnetin were identified in the crude yellow extracts obtained from SFE using liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 24 publications
(34 reference statements)
1
32
0
2
Order By: Relevance
“…values was estimated to be between 3.0% and 4.7% for each extract. Polyphenols are also included in rice bran (Ajitha, Mohanlal, Suresh, & Jayalekshmy, ; Nakornriab, Sriseadka, & Wongpornchai, ). These polyphenols may also contribute to ArO• scavenging.…”
Section: Discussionmentioning
confidence: 99%
“…values was estimated to be between 3.0% and 4.7% for each extract. Polyphenols are also included in rice bran (Ajitha, Mohanlal, Suresh, & Jayalekshmy, ; Nakornriab, Sriseadka, & Wongpornchai, ). These polyphenols may also contribute to ArO• scavenging.…”
Section: Discussionmentioning
confidence: 99%
“…Abdul-Hamid et al [10] found lycopene and β-carotene in the bran from bulk rice obtained from a commercial mill and Frei and Becker [7] measured β-carotene in colored and non-colored Asian landraces. Abdul-Hamid et al [10] identified β-carotene and lycopene in rice bran obtained from a local mill; Nakornriab et al [36] identified β-carotene in the brans of two Thai black rices.…”
Section: Identification Of Carotenoidsmentioning
confidence: 99%
“…Extensive studies have been reviewed on biological functions, preclinical tests and the structural determination of naturally occurring anthocyanins Cooke et al, 2005;. Among these studies, some have focused on anthocyanins contained in bran of black-coloured rice (Nakornriab et al, 2008;Revilla et al, 2009;Finocchiaro et al, 2010), as well as on anthocyanins' biological activities, which were mainly antioxidation. The quantitative information concerning anthocyanin pigments in black-coloured rice based on the use of effective instrumental methods has, however, been limited.…”
Section: Introductionmentioning
confidence: 99%